Habilidades directivas y desempeño laboral de los colaboradores del proyecto control y reducción del cultivo de la coca en el Alto Huallaga 2022 - Soria Da'Silva, Pedro (2023)
In the thesis report, the study objective has been formulated: to determine the relationship between management skills and job performance of the collaborators of the Coca Cultivation Control and Reduction Project in Alto Huallaga 2022, being an applied research with a non-specific design. experimental, where the population has been taken and shows 71 collaborators to whom the survey technique and the questionnaire were applied as an instrument. Coming to the conclusion that the managerial skills of the boss are regular. He tends to show courtesy and respect towards staff, encourages interpersonal growth, and always promotes positive change even in difficult situations. In addition, he is able to know the content of his presentations well, making them easy to understand. Work performance was evaluated as regular, since on some occasions they have the initiative to acquire new skills and broaden their horizons in the workplace; sometimes they carry out their work in an orderly and conscientious manner. Likewise, it was determined that there is a relationship, this was confirmed by the correlation coefficient (r=0.842) and the sig value (p=0.000), which establishes a significant correlation between the variables.